Boards of Directors, Top Management Compensation, and Shareholder Returns - Kerr, Jeffrey L.; Bettis, Richard A. (Academy of Management Journal, 1987)
According to the corporate governance process and agency theory, boards of directors should reward executives on the basis of financial returns to shareholders. Studies of this issue have been inconclusive, however, and have frequently employed arguable measures of shareholders' returns. This study employed time-event methodology, a technique from financial economics, to examine abnormal returns, which are returns to shareholders corrected for the movement of the overall market. Results suggest that neither variation in abnormal returns nor overall market movements influences compensation to top executives. Tentative explanations and implications for the role of boards of directors in evaluating and rewarding top management are discussed.